Galanin and Adrenomedullin Plasma Responses During Artificial Gravity on a Human Short-Arm Centrifuge - Winter, Julia; Laing, Charles; Johannes, Bernd; Mulder, Edwin; Brix, Bianca; Roessler, Andreas; Reichmuth, Johannes; Rittweger, Joern; Goswami, Nandu (Frontiers in Physiology, 2019)
Galanin and adrenomedullin plasma responses to head-up tilt and lower body negative pressure have been studied previously. However, to what extent short-arm human centrifugation (SAHC) affects these responses is not known. In this study, we assessed how the application of variable gradients of accelerations (ΔGz) via shifting of the rotation axis during centrifugation affects selected hormonal responses. Specifically, we tested the hypothesis, that cardiovascular modulating hormones such as galanin and adrenomedullin will be higher in non-finishers (participants in whom at least one of the pre-defined criteria for presyncope was fulfilled) when compared to finishers (participants who completed the entire protocol in both sessions) during SAHC exposure. Twenty healthy subjects (10 women and 10 men) were exposed to two g-levels [1 Gz and 2.4 Gz at the feet (Gz_Feet)] in two positions (axis of rotation placed above the head and axis of rotation placed at the heart level). Elevated baseline levels of galanin appeared to predict orthostatic tolerance (p = 0.054) and seemed to support good orthostatic tolerance during 1 Gz_Feet SAHC (p = 0.034). In finishers, 2.4 Gz_Feet SAHC was associated with increased galanin levels after centrifugation (p = 0.007). For adrenomedullin, the hypothesized increases were observed after centrifugation at 1 Gz_Feet (p = 0.031), but not at 2.4 Gz_Feet, suggesting that other central mechanisms than local distribution of adrenomedullin predominate when coping with central hypovolemia induced by SAHC (p > 0.14). In conclusion, baseline galanin levels could potentially be used to predict development of presyncope in subjects. Furthermore, galanin levels increase during elevated levels of central hypovolemia and galanin responses appear to be important for coping with such challenges. Adrenomedullin release depends on degree of central hypovolemia induced fluid shifts and a subject’s ability to cope with such challenges. Our results suggest that the gradient of acceleration (ΔGz) is an innovative approach to quantify the grade of central hypovolemia and to assess neurohormonal responses in those that can tolerate (finishers) or not tolerate (non-finishers) artificial gravity (AG). As AG is being considered as a preventing tool for spaceflight induced deconditioning in future missions, understanding effects of AG on hormonal responses in subjects who develop presyncope is important.